Carbohydrate content and season collection of cuttings from 'Roxo de Valinhos' fig tree - Souza, Jackson Mirellys Azevêdo [UNESP]; Leonel, Sarita [UNESP]; De Souza Silva, Marcelo [UNESP]; De Oliveira, Marcelo De Almeida [UNESP]; Martins, Rafaelly Calsavara [UNESP]; Bolfarini, Ana Carolina Batista [UNESP]; Ataíde, Elma MacHado (Lepidus Tecnologia, 2019)
Choosing the best season collection of cuttings is essential to have success with propagation, due mainly to carbohydrate content, since is a source of energy for roots and shoots development. In literature, there are no papers that associate the collection season of cuttings with carbohydrate contents in figs. Therefore, the current study aimed to evaluate carbohydrate contents and season collection of cuttings to propagate 'Roxo de Valinhos' fig tree. The experiment was conducted in a greenhouse; cuttings were collected in the first week of the following months: June, July, August and September. The design was in completely randomized blocks, with four replicates of 30 cuttings collected per season. The following traits were evaluated: carbohydrate content; percentage of root cuttings, bud cuttings, cuttings without bud and root; number of buds, leaves and roots per cutting; length of the largest root and bud; bud diameter; bud and root dry mass; and root volume. Results indicated high carbohydrate content in cuttings that were collected in August; therefore, the best month to collect cuttings of 'Roxo de Valinhos' fig tree in the city of São Manuel, state of São Paulo. This result is due to high percentage of rooted cuttings and better development. Furthermore, carbohydrate content mainly affects root growth; besides that, reducing sugars are the most important feature in the development of cuttings.
Keywords: Correlation; Cuttings; Ficus carica; Reducing sugars; Starch; Sucrose